Teachers’ Knowledge about the use of ICT in the ELT Classroom - Shahi, Dhruba Kumar (AMC Multidisciplinary Research Journal, 2022)
Information and Communication Technology (ICT) as a potential tool for enhancing the quality of education in Nepal and other countries. However, there is a lack of research examining secondary level English teachers’ knowledge in the integration of ICT. In this study, we aimed to investigate teachers’ knowledge in the use of ICT in secondary English classrooms. The study employed a quantitative method with a cross -sectional survey approach. It was conducted in Sudurpaschim province where the data were collected from 150 secondary English teachers through a questionnaire survey. The findings suggest that, to a large extent, secondary level English teachers have a largely inadequate knowledge of ICT and knowledge of ICT use in teaching. Based on the findings, we argue that it is crucial to improve English teachers’ knowledge of both aspects, and more training courses for teachers’ knowledge development are needed.